ANALISIS PERMINTAAN MINYAK GORENG CURAH DI PASAR FLAMBOYAN KOTA PONTIANAK - Zulkarnaen, Zulkarnaen; Yurisinthae, Erlinda; Aritonang, Marisi (Fakultas Pertanian, Universitas Janabadra, 2024)
This study aims to analyze the factors affecting consumer demand for bulk cooking oil at Pasar Flamboyan in Pontianak City. This research uses a descriptive method with a quantitative approach, data is analyzed through a multiple linear regression model. Data collected are sourced from both primary and secondary information, with the research location purposively chosen as Pasar Flamboyan in Pontianak City. Findings from this study indicate that the price of bulk cooking oil, the price of packaged cooking oil, income, and family size have a positive impact simultaneously on the desire to purchase bulk cooking oil at the research site. However, when analyzed partially, only the price of bulk cooking oil, the price of packaged cooking oil, and family size significantly influence the purchase decision, while income does not show an effect on the demand for bulk cooking oil at Pasar Flamboyan in Pontianak City.